A serum protein signature of APOE genotypes in centenarians. Issue 6 (5th August 2019) - Sebastiani, Paola; Monti, Stefano; Morris, Melody; Gurinovich, Anastasia; Toshiko, Tanaka; Andersen, Stacy L.; Sweigart, Benjamin; Ferrucci, Luigi; Jennings, Lori L.; Glass, David J.; Perls, Thomas T.
Abstract: The discovery of treatments to prevent or delay dementia and Alzheimer's disease is a priority. The gene APOE is associated with cognitive change and late‐onset Alzheimer's disease, and epidemiological studies have provided strong evidence that the e 2 allele of APOE has a neuroprotective effect, it is associated with increased longevity and an extended healthy lifespan in centenarians. In this study, we correlated APOE genotype data of 222 participants of the New England Centenarian Study, including 75 centenarians, 82 centenarian offspring, and 65 controls, comprising 55 carriers of APOE e 2, with aptamer‐based serum proteomics (SomaLogic technology) of 4, 785 human proteins corresponding to 4, 137 genes. We discovered a signature of 16 proteins that associated with different APOE genotypes and replicated the signature in three independent studies. We also show that the protein signature tracks with gene expression profiles in brains of late‐onset Alzheimer's disease versus healthy controls. Finally, we show that seven of these proteins correlate with cognitive function patterns in longitudinally collected data. This analysis in particular suggests that Baculoviral IAP repeat containing two (BIRC2) is a novel biomarker of neuroprotection that associates with the neuroprotective allele of APOE . Therefore, targeting APOE e 2 molecularly may preserve cognitive function. Abstract : This work correlates a large set of serum proteins with carriers of APOE e 2 allele from a study of human longevity that includes centenarians and their offspring. The analysis discovers a reproducible signature of 16 serum proteins in cis and trans with APOE alleles. Expression profiles of genes in the signature in brains distinguish late‐onset Alzheimer's disease (LOAD) patients from healthy controls. Some of these proteins correlate with patterns of cognitive function and could be new therapeutic targets of neuroprotection.